Unveiling the Role of Cross-Cultural and Cognitive Differences in Organizational Learning Mechanism of Technology-Acquiring Cross-Border Mergers and Acquisitions: Evidence From Emerging Market Enterprises - Chen, Kanxiang; Cheng, Xuanmei; Zhang, Run; Cillo, Giuseppe; Ragusa, Antonio (Frontiers in Psychology, 2022)
In recent years, cross-border mergers and acquisitions (M&As) of emerging market enterprises (EMEs) have increased rapidly, and many cross-border M&A have been conducted in the United States, Western Europe, and other developed countries. This new type of technology-acquiring cross-border M&A has several unique features. In particular, the cross-cultural differences between the home country and the host country and the cognitive differences between emerging markets and developed markets pose a huge challenge to the organizational learning of technology-acquiring cross-border M&A of enterprises from emerging markets. Based on this, the present study innovatively constructs an integrated theoretical model to explore the role of cross-cultural and cognitive differences in the organizational learning mechanism of technology-acquiring cross-border M&A in emerging markets. In this study, the partial least squares structural equation model (PLS-SEM) was used in an empirical study of 240 Chinese technology-acquiring cross-border M&A enterprises, and it was found that cultural and cognitive differences play an important role in technical ability and learning performance. The study also found that the interaction of cross-cultural differences between the home and host countries and the cognitive differences between the emerging and developed markets promoted the learning performance of cross-border M&A in the emerging markets. Based on the integration theory of cultural differences, cognitive differences, and technical ability, this paper unveils the role of cross-cultural and cognitive differences in organizational learning mechanisms of technology-acquiring cross-border M&A.